Tony and Cherie : A Special Relationship - Scott, Paul (London Sidgwick & Jackson, 2005)
A biography that looks at how the Blairs have survived life in Downing Street with all its stresses and strains. This book takes the reader on a journey from their first steps into the tatty environs of the flat in Number 11 to Blair's triumphant third term and increasing importance as an international statesman.
Include Index and Illustration
Keywords: Marriage -- Prime ministers -- Prime ministers' spouses